Biosynthesis and Characterization of SiO-Cochineal Dye Nanoparticles Based on Salak Frond Silica for Fingerprint Visualization Applications - Sri Adelila Sari; Feri Yuni Asiyah Kabeakan; Rani Febriana (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
Latent fingerprint visualization is a critical technique in modern forensic science that requires effective and environmentally sustainable coloring agents. This study reports synthesizing and characterizing a novel dyeing agent based on Cochineal insect extract combined with silica derived from salak (Salacca zalacca) bunch waste. It evaluates its application in fingerprint visualization. Cochineal extract was obtained via stepwise heating in a polar solvent, while silica was synthesized through carbonization, demineralization, destruction, and neutralization. The SiO–Cochineal nanoparticles were prepared using a stepwise thermal immobilization method, resulting in covalent bonding between the pigment and silica matrix. Structural and functional group characterization using FTIR confirmed the presence of Si–O–Si, O–H, and C=O groups, indicating successful integration. Application tests on latent fingerprints demonstrated that the composite powders produced sharp and distinct ridge patterns, particularly on non-porous substrates such as glass and optical discs. These findings suggest that SiO-Cochineal-based powders are effective for forensic applications and represent a promising green alternative for latent fingerprint visualization.